Optimization studies on esterification of waste cooking oil using sulfated montmorillonite clay acidic catalyst. (2021) - Devaraj Naik, B.; Udayakumar, M.
Abstract: Currently, refined edible oils are used to produce biodiesel with the help of a base catalyst. The most important problem with the base-catalyzed esterification process is that they produce soap when they have higher free fatty acids (FFA). The present study indicates that montmorillonite (k10) can be a significant catalyst prepared by the impregnation method using H2 SO4 in the ratio of 1:5. The prepared novel catalyst was characterized using XRD, FTIR and SEM-EDS techniques. The optimum conditions for esterification have been determined by applying RSM with CCD methodology for each significant variable like oil-methanol molar ratio, catalyst amount, reaction time and temperature. The optimum acid conversion of 80.8% was observed at an oil-methanol molar ratio of 1:12, amount of catalyst 6 wt% and 120 min of reaction time at 55 °C.